Effects of Intermittent Administration of Parathyroid Hormone (1-34) on Bone Differentiation in Stromal Precursor Antigen-1 Positive Human Periodontal Ligament Stem Cells. (16th March 2016) - Wang, Xiaoxiao; Wang, Yanlan; Dai, Xubin; Chen, Tianyu; Yang, Fanqiao; Dai, Shuangye; Ou, Qianmin; Wang, Yan; Lin, Xuefeng
Abstract : Periodontitis is the most common cause of tooth loss and bone destruction in adults worldwide. Human periodontal ligament stem cells (hPDLSCs) may represent promising new therapeutic biomaterials for tissue engineering applications. Stromal precursor antigen-1 (STRO-1) has been shown to have roles in adherence, proliferation, and multipotency. Parathyroid hormone (PTH) has been shown to enhance proliferation in osteoblasts. Therefore, in this study, we aimed to compare the functions of STRO-1(+) and STRO-1(−) hPDLSCs and to investigate the effects of PTH on the osteogenic capacity of STRO-1(+) hPDLSCs in order to evaluate their potential applications in the treatment of periodontitis. Our data showed that STRO-1(+) hPDLSCs expressed higher levels of the PTH-1 receptor (PTH1R) than STRO-1(−) hPDLSCs. In addition, intermittent PTH treatment enhanced the expression of PTH1R and osteogenesis-related genes in STRO-1(+) hPDLSCs. PTH-treated cells also exhibited increased alkaline phosphatase activity and mineralization ability. Therefore, STRO-1(+) hPDLSCs represented a more promising cell resource for biomaterials and tissue engineering applications. Intermittent PTH treatment improved the capacity for STRO-1(+) hPDLSCs to repair damaged tissue and ameliorate the symptoms of periodontitis.